Comparison of the Effectiveness of Olson’s Circumplex Model–Based Couple Therapy and Acceptance and Commitment Therapy (ACT) on Marital Burnout and Marital Self-Regulation in Couples with Conflict - Gholipour, Soheila; Jarareh, Jamshid; Jafari, Asghar (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of Olson’s Circumplex Model–based couple therapy and Acceptance and Commitment Therapy (ACT) on marital burnout and marital self-regulation in couples experiencing marital conflict. This study employed a quasi-experimental design with pretest, posttest, and follow-up assessments, including two experimental groups and one control group. The statistical population consisted of couples experiencing marital conflict who referred to counseling centers in Amol in 2024. A total of 48 participants (24 couples) were selected through convenience sampling and randomly assigned to two experimental groups and one control group. The first experimental group received ten sessions of Olson’s Circumplex Model–based couple therapy, and the second experimental group participated in eight sessions of ACT-based couple therapy. The control group did not receive any intervention during the study period. Data were collected using the Marital Conflict Questionnaire, the Marital Burnout Questionnaire, and the Marital Self-Regulation Questionnaire. Data were analyzed using multivariate analysis of covariance (MANCOVA), analysis of covariance (ANCOVA), repeated-measures ANOVA, and LSD post hoc tests in SPSS-27 at a significance level of .05. The results of MANCOVA indicated that both Olson-based couple therapy and ACT significantly reduced marital burnout and increased marital self-regulation compared to the control group (p < .001). ANCOVA results showed that, after controlling for pretest scores, the group effect was significant for marital burnout (F = 26.45, p < .001, η² = .664) and marital self-regulation (F = 24.63, p < .001, η² = .241). Post hoc comparisons revealed significant differences between the two experimental groups at posttest (p < .001), indicating differential magnitudes of effectiveness across outcomes. Both interventions are effective interventions for reducing marital burnout and enhancing marital self-regulation among couples experiencing conflict.